ANALYSIS OF RELATED FACTORS WITH COMPLETE BASIC IMMUNIZATION ONTODDLERS IN UJUNG BAWANG VILLAGE, ACEH SINGKIL - Safitri, Faradilla (Universitas Ubudiyah Indonesia, 2017)
Immunization is an effort to provide immunity to children by entering the vaccine into the body so that the body makes anti-substance to prevent certain diseases. Data from DinasKesehatan Aceh Singkil, immunization coverage in 2015 is 87.5%, but in Working Areas PuskesmasSingkil, the village where immunization coverage does not meet the Universal Coverage Immunization (UCI) standard is Ujung Bawang Village (69.0%). The purpose of this study was to analyze factors related to the completeness of basic immunization in under-five children in Ujung BawangVillage Aceh Singkil in 2017. Type of analytical research was cross-sectional approach. The populationswereall mothers who have toddlers as many as 42 people, sampling of this research was total population. Data collection was collected in 30 March to 14 April 2017. The research instrument used was questionnaire. Data analysisanalyzedbyusing univariate and bivariate. Univariate analysis showed 69.0% complete immunization toddler, 69.0% was low educated mothers, 71.4% was high knowledge mother, 90.5% was unemployed mother, 69.0% was mothers with children <3, 57.1% mothers was positive and 54,8% was distance of health service location The result of bivariate analysis produces education (P-value = 1,000), knowledge (p-value = 0.000), employment status (p-value = 1,000), number of children (p-value = 1,000) P-value = 0.173), attitude (p-value = 0.008) And affordability of health service (p-value = 0.354). The conclusion of this research is the correlation between knowledge and attitude with the completeness of basic immunization on toddlers while there are no relation of education, employment status, number of children and affordability of health service facilities with basic immunization completeness in children of Ujung Bawang Aceh Singkil 2017. Expected to the health officer of Aceh Singkil can make counseling accompanied by the distribution of brochures and the installation of banners on the importance of providing basic immunization to children.Keywords: Basic immunization, knowledge, attitude